Filtration in Pharmaceutical Industries and Role of Textile - Akhtarul Islam Amjad (Tekstilec)
Filtration is considered the keystone for clarification and control of contamination in pharmaceutical and biopharmaceutical manufacturing. From production to in-process to chemical and research laboratories to the purification of water for sterile and nonsterile products, all of which involve some form of filtration in order to achieve a good manufacturing practice (GMP). Textile materials possess a significant contribution to the pharmaceutical filtration system. Textile material in pharmaceutical filtration is used in the form of filter media or medium. Flexible in nature, large pore distribution and non-metallic properties of textile materials have led to widespread use as filter media for many years. In filtration processes, a proper selection of filter media/ membrane material is usually the most critical aspect for ensuring efficient separation. Generally, solid-liquid and solid-gas separation is done by the filter media. This paper emphasises solid-liquid filtration. Moreover, this paper reviews the water requirement, filtration processes and the role of textile in the filtration system of pharmaceutical industries. This paper also offers insight into the current market trend and COVID-19 impact on the pharmaceutical filtration industry. Furthermore, gathered information may be helpful to those studying and working in pharmaceutical engineering, filtration technology, and wastewater treatment and can get knowledge about filtration systems.